Impact of Government Health Expenditure on Economic Growth in Nigeria 1981 - 2016 - Yusuf, Patience (My University, 2020)
This study empirically examined the relationship between government health expenditure on economic growth in Nigeria using Gross Domestic Product (GDP) as a proxy to economic growth which is the dependent variable and the independent variables are Capital Expenditure on Health (CAPEXP) and Recurrent Expenditure on Health (RECEXP). The Error Correction Mechanism results showed that the system corrects to equilibrium at a speed of 43.40%. The study also employed the OLS regression analysis to estimate the model and the R2 showed a 94% significant relationship between government health expenditure and economic growth. The regression analysis results showed that the dependent variable (GDP) has; a positive and significant relationship witall the independent variables; every 1% unit increase in CAPEXP and RECEXP will increase economic growth by 140.1217 units and 190.7144 units respectively. Good public health is vital in any country, not only to maintain a healthy populace but also as a matter of national security. Given these findings, to ensure sustainable economic growth, it is recommended that there is the need for the Nigerian government to double its budgetary allocation to the health sector - through the setting up of a good administrative/monitoring team, the utilization of disbursed funds meant for capital projects can be closely monitored, especially in the area of procurement; adequate and equitable distribution of healthcare facilities should involve the interests of all citizens especially those in the rural centres. And to ensure efficient service delivery by the health/medical practitioners or workers, the government should ensure prompt payment of salaries and wages and other benefits of the health workers (doctors, nurses, lab technicians, etc), as this will go a long way in encouraging them to work more efficiently. Thereby, resulting in improved service delivery in the country.
Keywords: Economic Growth; Government Expenditure; Healthcare; Healthcare Demand; Healthcare Supply; Nigerian Economy